CCTV : From Light to Pixels - Damjanovski, Vlado, 1956- (Butterworth-Heinemann, 2014)
The new edition of CCTV, a high-level professional reference, is expanded to cover all video compression techniques used in the ever-increasing assortment of digital video recorders (DVRs) available on the market today. In addition to demystifying DVR technology, the third edition also clarifies the technology of data networking and explains various compression techniques. Along with all this, the book retains the particulars that made the previous editions convenient and valuable, including details of CCD cameras, lenses, coaxial cables, fiber-optics, and system design. Updated to address digital techniques, networking, and the Internet in closed-circuit television Includes brand new sections on CCTV networking, digital video recorders (DVRs), various video compression techniques, and understanding pixels and digital image quality. Fully illustrated with dozens of photographs, tables, checklists, charts, diagrams, and instructions.